Scale sensitivity and question order in the contingent valuation method - Henrik Andersson; Mikael Svensson (Örebro University School of Business, 2010)
This study examines the effect on respondents' willingness to pay to reduce mortality risk by the order of the question in a stated preference study. Using answers from an experiment conducted on a Swedish sample where respondents' cognitive ability was measured and where they participate in a contingent valuation survey it is found that scale sensitivity is the strongest when respondents are asked about a smaller risk reduction first ("Bottom-up" approach). This contradicts some previous evidence in the literature. It is also found that the respondents' cognitive ability is correlated with their answers being line with theoretical predictions. The latter being important for the validity of the answers. Hence, the results of this paper suggest that scale sensitivity is related to the order of the questions and to respondents' cognitive ability.
Keywords: D80; I10; Q51; 330; Cognitive ability; Contingent valuation; Mortality risk; Order effect; Scale sensitivity